P165 Survival of Patients with Lung Cancer Diagnosed at a Teaching Hospital in London, UK Between 2000 and 2010. (19th November 2012) - Clark, KEN; Rao, D; Birring, SS; Lal, R; Desai, S; Pomplun, S; Kelly, J; Atuchar, I; Barker, RD
Abstract : Background: Significant resources have been applied to improving outcomes for patients with lung cancer. Here we analyse trends in survival for patients diagnosed at our institution between 2000 and 2011. Methods: All patients with suspected intra-thoracic malignancy were discussed at a weekly multi-disciplinary meeting and logged in a bespoke database. Relevant diagnostic and staging parameters were recorded. Data items were defined according to the specifications of the Lucada dataset. Patients were grouped into sequential 2 year epochs according to the date they were first seen. Analysis was restricted to the major cell types; squamous cell, adenocarcinoma, small cell and probable lung cancer unknown histology, first seen between January 1st 2000 and January 1st 2010. Survival time was censored on the 1st September 2011. Univariate analyses with survival as the dependent variable included age group, sex, histological cell type, stage, performance status and epoch used the Kaplan-Meier technique. Multivariate analyses used Cox's proportional hazards model. Results: 1105 patients met the entry criteria and vital status was firmly ascertained for 1099 (99.5%). The median age was 71 years (range 32 – 96). 698 63.5% were men. Median survival increased from 195 (95% CI 148, 242) days to 231 days (95% CI 151, 311) p<0.001. In the 2000–1 cohort it took 412 days for 75% of the patients to die, in 2009–10 it took 839 days. In univariate analyses there were significant differences in survival in relation to all the variables. Patients with adenocarcinoma lived longer than other cell types. In multivariate analyses age group, epoch, stage and performance status but not histology and gender remained independent predictors of survival. Histology was confounded by epoch. Discussion: These data suggest that survival for patients with lung cancer has improved over the last few years. Patients with adenocarcinoma live longer than patients with other cell types. Elsewhere we have shown that the proportion of patients with adenocarcinoma has increased in our cohort with time. Taken together these data suggest that increased longevity of lung cancer patients may be in part due to a shift towards adenocarcinoma cell type but also another factor that has occurred more recently.